Transverse Isotropism of Cancellous Bone as a Two-phase Porous Structure - Haibin CHEN (Institute of Advanced Engineering and Science, 2012)
Since the cancellous bone displays a fluid-solid coupled porous structure, its solid matrix exhibits excellent osteogenic property and has been extensively used as the scaffold material of tissue-engineering bone. It is the aim of the present paper to examine the transversely isotropic behavior of cancellous bone. Correspondingly, a two-dimension image analysis method was developed to determine the distribution characteristics of cancellous bone porosity. The fresh behind-leg tibia of three swine were dissected to develop a total of 36 HE staining specimens of cancellous bone, which were subjected to different anatomical locations along the axial or lateral direction. All cancellous bone specimens or cut-sections were examined microscopically and processed quantitatively. The main results and conclusions are as follows: (a) The cancellous bone porosity is gradually decreased along the axial direction of tibia and approaching to the cortical bone, but almost constant along the lateral direction of tibia. Correspondingly, cancellous bone can be modeled as a transversely isotropic, liquid saturated porous solid．(b) The two-dimensional image analysis method is able to be used to relatively accurately determine the distribution characteristics of the cancellous bone porosity from different directions if the number of cancellous bone cut-sections is sufficient. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1282